(untitled) (Transactions on Additive Manufacturing Meets Medicine, 2023)
Digital workflow is an integral part of reconstructive dentistry [1, 2]. Modern intraoral scanners are capable of producing high-resolution 3D data sets as a basis for additive or subtractive CAD/CAM manufacturing of high-precision restorations made of ceramics, plastics or metals within a short time [3, 4]. Today, composite-based direct and indirect restorative materials can be stably polymerized to many solid surfaces with suitable bonding systems [5, 6]. Digital processes also play an important role in planning the ideal dental implants position based on three-dimensional data sets, as well as in the CAD/CAM-supported fabrication of various templates [7]. Following the example of reconstructive facial surgery, 3D-printed patient-specific implants enable the treatment of dental indications in which conventional implants reach their limitation ranges [8]. There are also approaches to use robots in dental implantology. A robot in a predefined position with the aid of navigation systems anchored in the bone has already implanted the first standard implants [9]. The stability of the implant is particularly important for long-term successful implant restoration from the beginning. In immediate implant placements, the bone volume has not yet changed after tooth extraction. Placing an implant in this extraction socket immediately results in a shape mismatch between the shape of the bone and the outer contour of the implant. This incongruence leads to reduced primary stability of the implant due to the lack of contact surface between the implant and the bone. The aim of this presentation is to highlight the status of the application areas of digital process chains and to present ideas for further indication areas. Author’s statement Conflict of interest: Authors state no conflict of interest. Animal models: N/A, Informed consent: N/A, Ethical approval: N/A References [1] P.C. Pott, M. Stiesch. Digitaler Workflow - computergestützt zur optimalen Patientenversorgung. BZB. Bayerisches Zahnärzteblatt, September 2017, 46 – 51 [2] D. Klering, M. Eisenburger, M. Stiesch, P.C. Pott. Die digitale intra- und extraorale Abformung. ZWR 2019;128:231-235 [3] S. Piechota, M. Stiesch, P.C. Pott. Additive Fertigungstechniken in der modernen, digitalen Zahnmedizin. ZWR 2018;127:44-47 [4] P.C. Pott, A. Rzasa, M. Stiesch, M. Eisenburger. Internal and marginal fit of modern indirect class II composite restorations. J Dent Mater Tech 2014;3:99-105 [5] P.C. Pott, M. Stiesch, M. Eisenburger. Influence of artificial aging on the shear bond strength of zirconia composite interfaces after pretreatment with three 10-MDP adhesive systems. J Dent Mater Tech 2016; 5(1):1-9 [6] P.C. Pott, T.S. Syväri, M. Stiesch, M. Eisenburger. Influence of non-thermal argon plasma on the shear bond strength of zirconia resin interfaces. J Adv Prosthod 2018;10:308-314 [7] B. Rahlf, F. Ulmer, M. Stiesch, N.C. Gellrich, P.C. Pott. "Triple-Win" in der Implantatprothetik durch koordinierte Kommunikation zwischen Patient, Zahnarzt und Chirurg. ZWR - Das Deutsche Zahnärzteblatt, 2016;125(4):144-149 [8] N.C. Gellrich, B. Rahlf, R. Zimmerer, P.C. Pott, M. Rana. A new concept for implant-borne dental rehabilitation or how to overcome the biological weak-spot of conventional dental implants? Head & Face Medicine, 2017;13:17 [9] S.L. Bolding, U.N. Reebye. Accuracy of haptic robotic guidance of dental implant surgery for completely edentulous arches. J Prosthet Dent 2022;128:639-647